Performing Blackface on the Newfoundland Stage: The Rossleys, Transnational Connections, and Early Twentieth Century Theatre in St. John’s - Quigley, Colleen; Templeton, Melissa (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (Graduate Centre for the Study of Drama, University of Toronto, 2020)
The subject of race does not often breach the surface of contemporary theatre in Newfoundland. When it does, racial prejudice tends to be presented in ways that absolve white Newfoundlanders of guilt while echoing Canadian nationalist sentiments that position racism, especially anti-black racism, outside the country’s borders (see Robert Chafe’s play Oil and Water). This kind of narrative oversimplifies Newfoundland’s complicated history, creating its own racist paradigms of ignorance that fail to acknowledge the institutional discrimination, international influences, and local prejudices that inform racial construction on the island.By contrast, this article considers how transnational racist ideologies shaped Newfoundland’s early theatre scene by looking at the unstudied popular performances of The Rossleys. The Rossleys, a vaudeville-style performance troupe active in St. John’s from 1911-1917, featured numerous acts that epitomized colonialist rhetoric surrounding race at that time. From Wild West-themed shows to Blackface Minstrelsy, The Rossleys performed derogatory stereotypes to the amusement of white Newfoundlanders. Their performances undermine contemporary idealized fictions that glorify Newfoundland and Canadian histories without adequate consideration of their racist pasts.Studying the Rossleys highlights the transnational dimensions of racial construction on the island. Newfoundland held a peculiar space in North America at that time—not yet a part of Canada, the future of this British Dominion was still uncertain. In addition, the Rossleys were international figures; the husband and wife team immigrated from Scotland and England to the US (where they were active performers on the vaudeville circuit) and eventually established their company in Newfoundland, regularly bringing acts from Europe and the US to local theatres. This article discusses how racial ideologies in Newfoundland’s early theatre scene were shaped by complex transnational networks, and in doing so, exposes erasures caused by patriotic imaginings of a racism-free Canada.